The influence of prostaglandin G2 on platelet ultrastructure and platelet secretion. - Gerrard, J. M. (1977)
Prostaglandin G2 (PGG2) is a labile endoperoxide produced physiologically following exposure of platelets to aggregating agents. We report here studies using isolated PGG2. This agent stimulates a concentration-dependent internal platelet contraction very similar to that produced by the calcium ionophore A23187. EDTA prevented platelet aggregation but did not prevent PGG2-stimulated internal contraction or secretion. In contrast, prostaglandin E1 and dibutyryl cyclic AMP inhich selectively labilizes platelet granules, was added to platelets together with PGG2 there was a superadditive effect on platelet secretion. Thus, granule labilization induced by PMA is a separable phenomenon and complementary to the effect of PGG2 on contraction. The ultimate degree of secretion is dependent on both processes. Studies using additional inhibitors supported the hypothesis that PGG2 activates platelets (either directly or following conversion to thromboxane A2) by transporting calcium from an intracellular store to the cytoplasmic site of the platelet contractile proteins.